Farmland bird decline is associated with a strong population limitation of open-habitat species - Reif, Jiří; Telenský, Tomáš; Klvaňa, Petr; Cepák, Jaroslav; Storch, David (Basic and applied ecology, 2025)
Farmland birds rank among organisms showing the steepest declines of their European populations. To combat these declines, it is essential to understand demographic mechanisms underlying the negative population trends. For this purpose, we employ a novel modelling approach on a long-term multispecies dataset collected by citizen scientists throughout Czechia. Using this approach, we calculated recruitment, adult survival and population growth rates for 13 farmland bird species on annual basis from 2004 to 2021, and related these demographic rates to species population trends estimated over the same period, as well as to their habitat preferences. We observed a negative relationship between recruitment and adult survival within most species. This relationship becomes increasingly more negative in species breeding in more open habitats. These species also showed steeper population declines and less positive correlation between adult survival and population growth rate than species breeding more woody habitats. These results indicate that the open-habitat farmland birds face strong population regulation. Under such regulation, higher adult survival in some years, that may occur due to, for instance, suitable weather conditions, does not leave much capacity for new recruits, and thus is immediately compensated by low recruitment. We suggest that these demographic processes are underpinned by decreasing carrying capacity of the open habitats which may occur due to shrub encroachment or afforestation of agricultural land that are widespread in Europe. At the same time, species preferring woody habitats enjoy increasing habitat availability in farmland which may lead to population increases over the long-term. Our results indicate that conservation actions are needed to improve the carrying capacity of the open habitats, especially during the breeding season. For example, some initiatives aiming for mitigation of climate change impacts by afforestation should be carefully reconsidered to avoid adverse impacts on open habitat species.